Peran Pramuka Dalam Penanaman Nilai-Nilai Pendidikan Karakter Pada Siswa SDN 060824 Sutrisno - Rizky Zulayha Siregar; Onyta Pioma Gabe Pardede; Fajar Siddik Siregar (Simpati, 2024)
The cultivation of character education values to students is very important. The results obtained based on initial observations at SDN 060824 Sutrisno are that when lining up before class there are still some students who are less orderly, when the teacher gives advice students are less focused, and when there are other students who make mistakes there are still students who laugh at them. Based on these problems, it is known that the values of character education are not yet present in students. This study has the aim of knowing how the role of scouts is to instill character education values at SDN 060824 Sutrisno. A qualitative approach was used in this study. To collect information using interview and observation methods. The results can be obtained after this study there is a change in the attitude of students of SDN 060824 Sutrisno with scout activities that have been carried out. The values of character education have begun to exist in students as a result can be brought into their environment. Within students there are character education values that have been developed, namely religious attitudes, honesty, tolerance, discipline, hard work, independence, friendly or communicative, care for the environment, social care and responsibility.